Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Overview - Gadallah, Neveen S.; Brothers, Denis J. (Zootaxa, 2020)
The current knowledge of the distribution and diversity of extant aculeate wasps (Aculeata excluding ants and bees) in the Arabian Peninsula (and Socotra) is reviewed. The number of species (1096 of which about 28% are apparently endemic) represents about 3% of the world fauna, with Crabronidae the most diverse family (about 35% of Arabian species). Most species (46%) are Afrotropical, 37% are Palaearctic, and 17% are Indo-Malayan (Oriental).